THE INFLUENCE OF LEADERSHIP, MOTIVATION, WORK CULTURE AND SPIRITUAL QUOTIENT ON JOB SATISFACTION AND ITS IMPACT ON THE PERFORMANCE OF THE NATIONAL AMIL ZAKAT AGENCY - Jaenuri, Andi; Reniati, Reniati; Hamsani, Hamsani (Program Studi Manajemen, Fakultas Ekonomi dan Bisnis, Universitas Komputer Indonesia, 2025)
This study aims to determine the influence of leadership, motivation, work culture, and spiritual intelligence on job satisfaction and its impact on the performance of the National Zakat Agency of the Bangka Belitung Islands Province. Quantitative methods with questionnaire instruments were used in this study. All members of the National Zakat Agency of the Bangka Belitung Islands Province became the population and sample. The questionnaire was tested with a measurement model and a structural model, then data analysis was carried out by hypothesis testing. The study finds that most of the independent variables did not affect job satisfaction or amil (zakat collectors) performance. the exception for job satisfaction, which affected the amil performance, and work culture, which was affected through job satisfaction. The benefits of this study are to provide insight for leaders and managers of the National Zakat Agency in improving amil performance through more effective strategies, such as strengthening work culture and increasing job satisfaction. For the community, the results of this study can be a reference in understanding the factors that influence the effectiveness of zakat management. Keywords: Leadership; Motivation; Work Culture; Spiritual Quotient; Job Satisfaction